(untitled) (Anclajes, 2019)
This article deals with concept of monstrosity and how it can be used to refer to certain sexual practices that use prostheses to increase pleasure within the BDSM -Bondage, Discipline, Sadism, Masochism- and fetishism. This reflection starts with the myths that have defined modern monsters passing to their application to certain dissenting practices which questions the patriarchal heteronormative system, after revealing how the aesthetic surgery relativizes the natural body.